Ambiguitas Status Korban dan Pelaku Pekerja Paksa Siber Lintas Negara dalam Hukum Pidana Internasional (Hakim: Jurnal Ilmu Hukum dan Sosial, 2026)
The rapid development of information technology has given rise to a new transnational crime pattern in which organized cross-border cybercrime syndicates force trafficking victims to carry out online fraud, including romance scams and fraudulent investment schemes. This phenomenon places law enforcement officers in a difficult position when determining whether an individual apprehended in such operations is a perpetrator of cybercrime or a victim of exploitation compelled to commit the offense. This research descriptively analyzes that confusion by drawing on the Palermo Protocol and several international human rights instruments. Using a normative legal research method with statutory and conceptual approaches, this study finds that Article 3 of the Palermo Protocol provides a framework for victim identification through the elements of act, means, and purpose of exploitation, yet the Protocol does not explicitly regulate the non-punishment principle, leaving its application dependent on derivative instruments such as the ASEAN Convention Against Trafficking in Persons and international human rights law. The victim-perpetrator ambiguity can be minimized through the application of coercion, absence of reasonable alternative, and proportionality criteria, alongside strengthened early identification capacity among cross-border law enforcement agencies. This study recommends harmonizing national law with the non-punishment principle and strengthening international legal cooperation to reach the organizers who control these syndicates.